Rescue the Surviving Souls : The Great Jewish Refugee Crisis of the Seventeenth Century - Teller, Adam (Book collections on Project MUSE., 2020)
"The mid-seventeenth century witnessed an enormous wave of Jewish refugees and forced migrants from the wars of the Polish-Lithuanian Commonwealth, who spread across the Jewish communities of Europe and Asia. A series of wars that hit the Polish-Lithuanian Commonwealth-the Khmelnytsky uprising of 1648; the Muscovite invasion that begin in 1654; and the Swedish incursion from 1655 to 1660-all together forced many Jews out of their homes. Though not the direct targets of the combatants, within a short time many were deeply involved in the conflicts, some becoming victims of violence and some becoming arms-bearing participants. But most became refugees and forced migrants. These refugees posed a huge social, economic and ethical challenge to the Jewish world. In an unprecedented manner, the Jewish centers around Europe answered this challenge and, both individually and jointly, organized relief for the Polish-Lithuanian Jews in all the different places they now found themselves. The need for concerted action on behalf of the Polish Jewish refugees strengthened ties between communities across Europe, and significantly increased the range of communal co-operation. The book moves through the three different environments the refugees found themselves in. The first part looks at the refugees who remained within the Polish-Lithuanian Commonwealth, probing the local and regional policies of relief that would eventually prove so successful in helping them overcome the traumas of their past. The second examines the Jews who were brought to the slave markets of Constantinople, and then redeemed there by newly developed philanthropic systems that had raised the money to do so. The third examines the fate of the Jews who fled to Central and Western Europe, examining tensions that developed within the local Jewish populations between the need to help the refugees and a basic antipathy born of cultural difference. In each case, a web of inter-communal connections was created to help support the refugees-bringing different parts of the Jewish world into an extraordinary level of purposeful contact, and paving the way for similar organization in the future. As a result, the seventeenth century communities set in motion processes of change that would eventually be refashioned into the globalized Jewish world we know today"--